Long-range transcriptional regulation by the p110 CUX1 homeodomain protein on the ENCODE array - Vadnais, Charles (BioMed Central, 2013)
BACKGROUND: Overexpression of the Cut homeobox 1 gene, CUX1, inversely correlates with patient survival in breast cancers. Cell-based assays and molecular studies have revealed that transcriptional regulation by CUX1 involves mostly the proteolytically processed p110 isoform. As there is no antibody specific to p110 CUX1 only, an alternate strategy must be employed to identify its targets. RESULTS: We expressed physiological levels of a tagged-p110 CUX1 protein and performed chromatin affinity purification followed by hybridization on ENCODE and promoter arrays. Targets were validated by chromatin immunoprecipitation and transcriptional regulation by CUX1 was analyzed in expression profiling and RT-qPCR assays following CUX1 knockdown or p110 CUX1 overexpression. Approximately 47% and 14% of CUX1 binding sites were respectively mapped less than 4 Kbp, or more than 40 Kbp, away from a transcription start site. More genes exhibited changes in expression following CUX1 knockdown than p110 CUX1 overexpression. CUX1 directly activated or repressed 7.4% and 8.4% of putative targets identified on the ENCODE and promoter arrays respectively. This proportion increased to 11.2% for targets with 2 binding sites or more. Transcriptional repression was observed in a slightly higher proportion of target genes. The CUX1 consensus binding motif, ATCRAT, was found at 47.2% of the CUX1 binding sites, yet only 8.3% of the CUX1 consensus motifs present on the array were bound in vivo. The presence of a consensus binding motif did not have an impact on whether a target gene was repressed or activated. Interestingly, the distance between a binding site and a transcription start site did not significantly reduced the ability of CUX1 to regulate a target gene. Moreover, CUX1 not only was able to regulate the next adjacent gene, but also regulated the gene located beyond this one as well as the gene located further away in the opposite direction. CONCLUSION: Our results demonstrate that p110 CUX1 can activate or repress transcription when bound at a distance and can regulate more than one gene on certain genomic loci.